(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2022)
The Ethiopian government has a package of encouraging youths to participate in small and micro agricultural enterprises by giving legal certificate for youths who were organized in-group to start the business by providing financial supports in terms of credit. However, youths are less willing to participate in agricultural enterprises. Even after being organized into groups and having supports from government, some of them were not starting the business and some were interrupting the business they have been organized. Due to these, huge amount of money from the government, which was allocated for this purpose, is not being used as expected. Therefore, this study was intended to assess factors affecting rural and peri-urban youth participation in agricultural enterprises in Bena-Tsemay and Debubi Ari woreda of south omo zone. Two-stage sampling technique was used to select 155 sample households. Logit model was used to analyze determinants of youth’s participation in agricultural enterprises. The result of this study indicated that 32.3% respondents were participated and 67.7% were not participated in enterprises. Econometric results revealed that variables such as farm size, institutional capacity building, and weather road significantly affected youths’ participation in agricultural enterprises at 1% and 5% significance level. The study recommends that the provision of land for the agricultural enterprises should consider the size/type of the enterprises that youth are willingness to participate. The government should specify the institution/sector to enterprise type and consideration of all-weather roads for each enterprise type during organizing youth in different agricultural enterprises is important. Int. J. Agril. Res. Innov. Tech. 12(1): 84-93, June 2022